Debt Management Performance Assessment : Kyrgyz Republic - World Bank Group (World Bank, Washington, DC, 2016)
The Kyrgyz Republic became a parliamentary democracy in 2010 following political turmoil and ethnic unrest. Kyrgyz Republic’s economy has been resilient; however, the growth momentum of the past few years has been declining due to the difficult global economic environment and regional conflicts’ spillover effects on the country. While the shift provided a drive for critical fiscal reforms, financial sector reforms turned out to be challenging. The country successfully completed a three-year arrangement under the Extended Credit Facility in 2014. During the period, macro-economic stability was restored, and growth picked up. Inflation was kept below 10 per cent throughout the program. However, deepening economic crisis in Russia, adverse weather and the initial impact of the accession to the Eurasian Economic Union were the key contributing factors to the worsening outlook in 2015. Weaker demand in Russia and Kazakhstan adversely affect the exports and re-export sectors. Remittances from workers in Russia and Kazakhstan, which contribute about 30 percent of the country’s economy, have slowed down, and are expected to decline by more than 10 percent in 2015.